Aligning the Principles of Flexibility and Accountability in the Design of Homeschooling Implementation Policies - Fitriah, Amaliah; Widiputera, Ferdi; Pasaribu, Ernawati; Kristi, Ellen (Lembaran Ilmu Kependidikan, 2024)
Homeschooling is an educational option for children outside the school system that is practiced in various countries. In Indonesia, there is a trend towards an increasing number of homeschoolers. Homeschoolers value the flexibility in structure and content that homeschooling provides, which is not usually available in traditional schools. in traditional schools. One of the main challenges in formulating policies for implementing home schools is harmonizing the principles of flexibility and accountability. This research uses a mixed methods approach to obtain comprehensive data and provide a complete understanding. The harmonization of the Draft Regulations on the Implementation of Home Schools revealed that the state's interests in promoting home school accountability can be balanced with the interests of parents who desire flexibility. This allows for the proper fulfillment of the rights of homeschooled children. The results of the Focus Group Discussion (FGD) on the draft regulations for implementing home schools, conducted in Yogyakarta, Medan, and Balikpapan on November 9-11, 2022, showed that respondents were concerned about the principles of flexibility and accountability. Four issues were identified: homeschooling registration, scope of homeschooling material, recognition of past learning, and changing track.